2010
DOI: 10.1111/j.1600-0897.2010.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HLA‐G5 Plasmatic Levels During Pregnancy and Relationship with the 14‐bp Polymorphism

Abstract: Plasmatic HLA-G5 levels do not change during pregnancy and its concentration depends on 14-bp polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…Denmark [18] Pre-eclampsia +14-bp/À14-bp exon 8 +/+14-bp fetal genotype associated with pre-eclampsia Denmark [20] IVF +14-bp/À14-bp exon 8 +/+14-bp genotype associated with unsuccessful treatment Denmark [23] Birth weight +14-bp/À14-bp exon 8 +/+14-bp genotype associated with higher birth weight Denmark [21] HLA-G isoforms G1 and G5 and IVF 5 0 URR and 3 0 UTR regions Polymorphisms influenced sHLA-G expression India [8] RSA +14-bp/À14-bp exon 8 NS China [12] RSA +14-bp/À14-bp exon 8 +14-bp allele more frequent in female patients China [9] RSA +14-bp/À14-bp exon 8 NS Brazil [19] Pre-eclampsia +14-bp/À14-bp exon 8 À/À14-bp genotype conferred protection against pre-eclampsia China [16] sHLA-G expression +14-bp/À14-bp exon 8 sHLA-G expression lower in +/+14-bp than À14-bp carrier Norway [10] Pre-eclampsia +14-bp/À14-bp exon 8 NS Poland [22] IVF Promoter region and +14-bp/À14-bp exon 8 +/À14-bp genotype associated with IVF failure Brazil [13] RSA +14-bp/À14-bp exon 8 +/+14-bp genotype more frequent in controls Spain [17] HLA-G5 level +14-bp/À14-bp exon 8 +14-bp allele associated with the presence of the HLA-G5 isoform IVF: in vitro fertilization. NS: not significant.…”
Section: Countrymentioning
confidence: 99%
See 1 more Smart Citation
“…Denmark [18] Pre-eclampsia +14-bp/À14-bp exon 8 +/+14-bp fetal genotype associated with pre-eclampsia Denmark [20] IVF +14-bp/À14-bp exon 8 +/+14-bp genotype associated with unsuccessful treatment Denmark [23] Birth weight +14-bp/À14-bp exon 8 +/+14-bp genotype associated with higher birth weight Denmark [21] HLA-G isoforms G1 and G5 and IVF 5 0 URR and 3 0 UTR regions Polymorphisms influenced sHLA-G expression India [8] RSA +14-bp/À14-bp exon 8 NS China [12] RSA +14-bp/À14-bp exon 8 +14-bp allele more frequent in female patients China [9] RSA +14-bp/À14-bp exon 8 NS Brazil [19] Pre-eclampsia +14-bp/À14-bp exon 8 À/À14-bp genotype conferred protection against pre-eclampsia China [16] sHLA-G expression +14-bp/À14-bp exon 8 sHLA-G expression lower in +/+14-bp than À14-bp carrier Norway [10] Pre-eclampsia +14-bp/À14-bp exon 8 NS Poland [22] IVF Promoter region and +14-bp/À14-bp exon 8 +/À14-bp genotype associated with IVF failure Brazil [13] RSA +14-bp/À14-bp exon 8 +/+14-bp genotype more frequent in controls Spain [17] HLA-G5 level +14-bp/À14-bp exon 8 +14-bp allele associated with the presence of the HLA-G5 isoform IVF: in vitro fertilization. NS: not significant.…”
Section: Countrymentioning
confidence: 99%
“…reviews 17 studies that have reported on the 14-bp ins/del polymorphism in exon 8 of HLA-G and its association with various pregnancy complications. Out of five studies that focused on recurrent spontaneous abortion (RSA) [8,9,[11][12][13], four reported a link with mRNA expression [14][15][16][17], four with pre-eclampsia [10,18,19], three with IVF treatment [20][21][22] and one with birth weight [23].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed no difference in HLA-G5 levels between pregnant women and control women, and levels of HLA-G5 did not seem to change during pregnancy. However, HLA-G5 levels were higher among women carrying the 14 ins polymorphism either displaying heterozygosity or homozygosity than women without the 14 ins allele [55]. …”
Section: Hla-g Polymorphisms In Relation To Alternative Splicing Amentioning
confidence: 99%
“…El polimorfismo -201G>A (rs1233333) se localiza cerca del elemento RREB-1, el cual regula la baja transcripción del gen HLA-G (8). El polimorfismo 14-pb del/ins (rs66554220) se encuentra en la posición 3741 de la región 3' no traducida del gen HLA-G. La presencia del alelo 14pb ins provoca una deleción de 92 pb que influye en la estabilidad del ARNm y causa menor producción de HLA-G (13)(14)(15). Por tanto, el objetivo de este estudio es analizar la asociación de los polimorfismos -725C>G (rs1233334), -201G>A (rs1233333) y 14pb del/ins (rs66554220) del gen HLA-G en mujeres mexicanas con PGR.…”
Section: Introductionunclassified